Qualitative research in health care - Mays, Nicholas; Pope, Catherine (Hoboken : John Wiley and Sons, Inc., 2020)
Now in its fourth edition, this concise, accessible, and authoritative introduction to conducting and interpreting qualitative research in the health care field has been fully revised and updated. Continuing to introduce the core qualitative methods for data collection and analysis, this new edition also features chapters covering newer methods which are becoming more widely used in the health research field; examining the role of theory, the analysis of virtual and digital data, and advances in participatory approaches to research. Qualitative Research in Health Care, 4th Edition looks at the interface between qualitative and quantitative research in primary mixed method studies, case study research, and secondary analysis and evidence synthesis. The book further offers chapters covering: different research designs, ethical issues in qualitative research; interview, focus group and observational methods; and documentary and conversation analysis--Publisher's description.
The role of theory in qualitative research -- Ethical issues in qualitative research -- Interviews -- Focus groups -- Observational methods -- Documentary analysis -- Digital data and online qualitative research -- Analysis -- Conversation analysis -- Synthesising qualitative research -- Mixed methods research -- Case studies -- Participatory research in health care -- Quality in qualitative research.
Includes bibliographical references and index.
Keywords: Quality Assurance, Health Care; Data Collection; Health Services Research; Qualitative Research; Research Design